2005
DOI: 10.1038/sj.bmt.1705078
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of unrelated allogeneic bone marrow transplantation: results from the randomized clinical trial of T-cell depletion vs unmanipulated grafts for the prevention of graft-versus-host disease

Abstract: Summary:Unrelated-donor marrow transplantation is a potential option for transplant candidates lacking a compatible related donor. The T-cell Depletion Study compared the 3-year disease-free survival for patients receiving T-celldepleted (TCD) donor marrow (n ¼ 203) vs unmanipulated donor marrow with methotrexate and cyclosporine (M/C) (n ¼ 207). Hospital costs during index admission were documented with billing data, while hospital costs during subsequent 6-month follow-up were estimated from case report form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The universal application of allogeneic transplantation is limited by the cost of the procedure, which increases with the use of unrelated donors. [3][4][5][6] The donor search and the inpatient care during the fi rst 100 days following a transplant account for the majority of the costs, and severe complications post-transplant also increase costs. 5 However, the high degree of effectiveness in certain patients results in a cost-effectiveness ratio that is comparable to that of other accepted complex medical interventions, 3 and its role should be examined in the context of emerging pharmacological interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The universal application of allogeneic transplantation is limited by the cost of the procedure, which increases with the use of unrelated donors. [3][4][5][6] The donor search and the inpatient care during the fi rst 100 days following a transplant account for the majority of the costs, and severe complications post-transplant also increase costs. 5 However, the high degree of effectiveness in certain patients results in a cost-effectiveness ratio that is comparable to that of other accepted complex medical interventions, 3 and its role should be examined in the context of emerging pharmacological interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al reported significantly lower costs ($113 000 vs $155 000 in 2000 USD, P Ͻ .001) with T celldepleted grafts in a single-center comparative analysis, but the economic substudy of the randomized TCD trial conducted by National Heart, Lung, and Blood Institute found comparable costs between the TCD and unmanipulated donor arms ($145 115 vs $141 981 in 2001 USD, respectively; P ϭ .63). 17,20 The National Heart, Lung, and Blood Institute trial reported that, although TCD of the donor graft reduced the short-term costs, frequent hospitalizations and higher average number of hospital days resulting from infectious complications in the first 6 months after transplantation appeared to offset any savings seen with the initial transplantation stay.…”
Section: Transplant Factorsmentioning
confidence: 99%
“…[17][18][19][20] Many studies exclude costs of donor identification/stem cell procurement and patient evaluation for transplantation eligibility. [21][22][23][24] A few studies have looked at the out-of-pocket cost burden in HCT patients.…”
Section: Why Do Costs Matter?mentioning
confidence: 99%
“…Despite the intensive research in the field and high cost of the procedure, there have been very few investigations and publications on the cost of HSCT. [3][4][5][6][7] We have previously reported the total costs over 5 years after HSCT in 93 patients transplanted in 1998 and 1999 at our unit. 8 We found that higher costs of HSCT were associated with acute leukaemia, G-CSF prophylaxis, hospital care as opposed to home care, myeloablative conditioning (MAC) as opposed to reduced-intensity conditioning (RIC) and major transplantrelated complications.…”
Section: Introductionmentioning
confidence: 99%